Holography, 3D Imaging and 3D Display - Poon, Ting-Chung; Zhang, Yaping; Cao, Liangcai; Yoshikawa, Hiroshi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Modern holographic techniques have been successfully applied in many important areas, such as 3-D inspection, 3-D microscopy, metrology, and profilometry, augmented reality, and industrial informatics. This Special Issue covers selected pieces of cutting-edge research works, ranging from low-level acquisition, to high-level analysis, processing, and manipulation of holographic information. The Special Issue also serves as a comprehensive review of existing state-of-the-art techniques in 3-D imaging and 3-D display, as well as broad insights into the future development of these disciplines. The Special Issue contains 25 papers in the field of holography, 3-D imaging, and 3-D display. All the papers underwent substantial peer review under the guidelines of Applied Sciences.